The Induced Magnetosphere of Mars: Asymmetrical Topology of the Magnetic Field Lines. Issue 22 (27th November 2019) - Dubinin, E.; Modolo, R.; Fraenz, M.; Päetzold, M.; Woch, J.; Chai, L.; Wei, Y.; Connerney, J. E. P.; Mcfadden, J.; DiBraccio, G.; Espley, J.; Grigorenko, E.; et al.
Abstract: An asymmetrical pileup of the interplanetary magnetic field leads to an additional draping of the field lines in the opposite direction to the motional electric field. Such a draping and the associated magnetic field forces push the ionosphere plasma in the transverse direction opening a passage for an ion trail which contains dense and slowly moving plasma. We found that wrapping of the field lines around Mars starts in the hemisphere pointing in the direction of the motional electric field and propagates to the opposite hemisphere where the cross‐flow component of the draped interplanetary magnetic field changes sign in a broad area accompanied by the formation of loops of closed field lines. Reconnection near Mars accompanied by the generation of plasma vortices imposes serious constraints on the ion dynamics and their escape through the tail. The existence of all these features is confirmed by hybrid simulations. Key Points: Additional draping of the field lines in the opposite direction to the motional electric field appears Ion trail that contains dense and slowly moving tailward plasma arises Wrapping of the field lines is accompanied by the formation of loops of closed field lines and plasma vortices